Reliability Evaluation and Analysis of Mobile Ad Hoc Networks - Deepak Kumar Panda; Ranjan Kumar Dash (Institute of Advanced Engineering and Science, 2017)
The paper addresses the reliability problem of mobile ad hoc networks under link and node failure model. Node reliability is calculated as a function of no. of neighbor nodes, packet success rate, and device type and packet size. The presence of a link between any node pair is binary and its reliability is computed considering the distance between nodes and signal-to-noise ratio (SNR). An efficient algorithm is proposed to analyze and calculate the reliability of mobile ad hoc networks considering multiple routes from source and destination nodes. The effect of different parameters on node reliability and link reliability are analyzed and discussed. The network is simulated and analyzed using INET frame work. Reliability of two distinct cases of this simulation is evaluated. The simulated results and discussions ensure that evaluation of the reliability of any mobile ad hoc networks can be done easily and in an efficient manner by the proposed method.